Rural Community in Indonesia in their Fight for Governance Transparency through Radio - SJUCHRO, DIAN WARDIANA; ANDUNG, PETRUS ANA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The existence of PASS Community Radio or Radio Komunitas PASS (Rakom PASS) in Katapang District, West Java, Indonesia is unique. This article aimed to analyze how Rakom PASS as a communication medium between the local government and Katapang District of Bandung Regency created governance transparency. The case study method was used. As a result, it was discovered that the existence of Rakom PASS succeeded in promoting the creation of transparency and good governance in the Ketapang District. Furthermore, Rakom PASS has proven to be able to encourage a healthy, dialogical and constructive public space in the local community life.RESUMEN La existencia de PASS Community Radio o Radio Komunitas PASS (Rakom PASS) en el distrito de Katapang, Java Occidental, Indonesia, es única. Este artículo tuvo como objetivo analizar cómo Rakom PASS como medio de comunicación entre el gobierno local y el distrito de Katapang de Bandung Regency, creó transparencia en la gobernanza. Se utilizó el método de estudio de caso. Como resultado, se descubrió que la existencia de Rakom PASS logró promover la creación de transparencia y buen gobierno en el distrito de Ketapang. Además, Rakom PASS ha demostrado ser capaz de fomentar un espacio público saludable, dialógico y constructivo en la vida de la comunidad local.